Neural oscillations under binocular rivalry: a brain activity pattern formation perspective - D. Frank, T.; I. Galenko, P. (International Journal of Physical Research, 2021)
Binocular rivalry is a phenomenon in which individuals react to two overlaid images that are presented to both eyes of the individuals as if the two images were presented one after each other in time in a repetitive fashion. Recently, human brain activity has been measured during binocular rivalry. Previously reported brain activity data was evaluated and modeled from a human pattern formation perspective that states that the human brain in binocular rivalry experiments acts as a neural self-oscillator. The neural self-oscillator forms and dissolves brain activity patterns related to the two images in an alternating, rhythmic self-organized fashion. Task-related oscillatory components hidden in the brain activity raw data were identified using power spectral analysis. Those oscillatory components were subsequently modelled using a previously developed mathematical model for brain activity self-oscillations. The identified task-related oscillatory components showed similar power spectrum functions for both brain activity patterns. A reciprocal relationship between the amplitudes of the two patterns was found. The oscillator model was able to reproduce the power spectrum functions when noisy perturbations were taken into account.Â Â